Efektivitas Physics Interactive Multimedia pada Materi Listrik Bolak-Balik untuk Meningkatkan Literasi Digital Menggunakan Flipped Learning - Tirtandro Meda (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study aims to examine the effectiveness of using Physics Interactive Multimedia (PhysIM) in improving digital literacy and facilitating deep learning through the Flipped Learning model on Alternating Current topics. The research method used was a quasi-experiment with a Pretest-Posttest Control Group Design. The study was conducted at SMAN 2 Wates in the 2025/2026 academic year with Grade XII MIPA students divided into three classes: XII A (Experiment I with PhysIM + Flipped Learning), XII B (Experiment II with PowerPoint + Direct Instruction), and XII D (Control with Textbooks). Data collection instruments used validated digital literacy tests and critical thinking skills tests. Data analysis used the General Linear Model (GLM) and Normalized Gain (N-Gain). The results showed that class XII A implementing PhysIM with the flipped learning strategy achieved the highest N-Gain score on digital literacy (0.65), significantly different compared to classes XII B and XII D. The conclusion of this study is that the integration of PhysIM in the flipped learning ecosystem is effective in transforming students' roles from passive receivers to active learners who are digitally literate and capable of deep thinking.